Pemberdayaan Kelompok Tani untuk Penguatan Manajemen Lahan dan Agribisnis Hortikultura di Desa Jeruk Kabupaten Boyolali - Bistok Hasiholan Simanjuntak; Yoga Aji Handoko; Donna Setiawati; Priskilah Febi Widya Ningrum; Esther Sheliena; Alfred Jansen Sutrisno; Damara Dinda Nirmalasari Zebua; Dina Rotua Valentina Banjarnahor; Suprihati (Politeknik Piksi Ganesha Indonesia, 2026)
Jeruk Village, Selo Subdistrict, Boyolali Regency, is a highland agricultural area facing challenges such as sloping land erosion, low conservation knowledge, limited climate adaptation, and weak bargaining power of farmers. The Community Empowerment Program by Students (PMM) through Community Service Program (KKN) was implemented to empower the Bangun Tani 2 and Tani Mulyo 2 Farmer Groups by involving 32 Agrotechnology and Agribusiness students from Satya Wacana Christian University in September–October 2025. Activities included socialization, environmentally friendly technology training, mentoring, soil block making, biopesticide and biofertilizer production, education on sloping land conservation using terraced models, as well as post-harvest training and digital marketing. The evaluation showed an increase in farmers' understanding and skills based on pre-test and post-test scores. This program enhances farmers' independence, reduces dependence on external inputs, promotes product value addition, and expands market access through digital platforms, thereby potentially becoming a sustainable empowerment model for highland regions.